2019
DOI: 10.9734/ejmp/2019/v28i330135
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Phytochemical and Anticancer Activities of Epiphytic Orchid Aerides odorata Lindl.

Abstract: Aim: The present study was carried out to evaluate the phytochemical composition and anticancer activities of leaf extract of Aerides odorata Lour., a widely distributed epiphytic herb found in the Eastern Ghats of Vizianagram district. Methodology: The solvents like n-hexane, ethyl acetate and methanol were used to extract dried leaf material of A. odorata. These extracts were analysed for phytochemical constituents by GC-MS analysis and in vitro anticancer activity was done against two cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Differences in the presence of phytochemical substances in root extracts may be related to the compound's solubility in the solvent used (Bako et al, 2005). The results of this study are consistent with those of several previous investigations that have also identified alkaloids, carbohydrates, coumarins, flavonoids, phenols, steroids, tannins, and terpenoids in a variety of orchid species, including Acampe praemorsa (Suja & Williams, 2016), Aerides odorata (Katta et al, 2019), Cymbidium aloifolium (Shubha & Chowdappa, 2016), Luisia zeylanica (Sohag et al, 2017) and Vanda tessellata (Biswas & Sinha, 2020).…”
Section: Preliminary Phytochemical Analysissupporting
confidence: 90%
“…Differences in the presence of phytochemical substances in root extracts may be related to the compound's solubility in the solvent used (Bako et al, 2005). The results of this study are consistent with those of several previous investigations that have also identified alkaloids, carbohydrates, coumarins, flavonoids, phenols, steroids, tannins, and terpenoids in a variety of orchid species, including Acampe praemorsa (Suja & Williams, 2016), Aerides odorata (Katta et al, 2019), Cymbidium aloifolium (Shubha & Chowdappa, 2016), Luisia zeylanica (Sohag et al, 2017) and Vanda tessellata (Biswas & Sinha, 2020).…”
Section: Preliminary Phytochemical Analysissupporting
confidence: 90%
“…Aerides odorata memiliki infloresens berwarna putih, ungu, atau merah muda yang indah dan harum (Hongthongkham & Bunnag 2014). Anggrek kuku macan juga bermanfaat mengobati nyeri dada, masalah lambung, penyakit kulit, tuberkulosis, luka, infeksi telinga dan hidung, pneumonia, peradangan serta antikanker (Katta et al 2019).…”
Section: Pendahuluanunclassified
“…Other orchid extracts that are effective against breast cancer (MCF-7) are those from Eulophia nuda tubers [141], leaves of Aerides odorata [142], and leaves of Vanilla [143]. It is hypothesized that the cytotoxic activity is related to the synergistic action of the phytoconstituents present in these species [141].…”
Section: The Anticancer Activity Of Plant Extracts From Orchidaceaementioning
confidence: 99%